Psychiatric Morbidity in Psoriasis and Vitiligo in Two Tertiary Hospitals in Bangladesh (Bangabandhu Sheikh Mujib Medical University Journal, 2011)
Background: Many of the established skin diseases give rise to psychiatric disorders notably psoriasis and vitiligo. In Bangladesh, no study has yet been reported on psychiatric morbidity among psoriasis and vitiligo patients. Objectives: The objective of the study was to see the psychiatric morbidities in two chronic skin diseases, psoriasis and vitiligo, in Bangladesh. Methods: This was a cross sectional, analytical and comparative study. It was conducted to see whether psychiatric morbidity was higher among patients with psoriasis than that of vitiligo. Specific types of psychiatric disorders were identified by consultant psychiatrist assigned as per criteria of (Diagnostic and Statistical Manual for Mental and Behavioural Disorders-Fourth Edition)DSM-IV among 50 patients with psoriasis and same number of patients with vitiligo and were compared. Study places were the Departments of Dermatology and Venereology, Bangabandhu Sheikh Mujib Medical University (BSMMU) and Dhaka Medical College Hospital (DMCH) in Dhaka city. Results: Among the two dermatological conditions, psychiatric disorders were found 25 (50%) in psoriatic patients and 12 (24%) that in vitiligo patients. The proportion of major depressive disorders (MDD) was higher among psoriasis patients 15(30.0%) compared to vitiligo patients 04(8.0%). However, no statistical difference was found between two groups of patients in terms of anxiety disorders (8% in psoriasis and 12% in vitiligo patients). In patients with psoriasis, MDD was found highest (30.0%) followed by anxiety disorders (8.0%), adjustment disorder (4.0%) and somatoform disorder not otherwise specified (2.0%). Whereas, among the vitiligo patients, anxiety disorder was found highest (12.0%) followed by MDD (8.0%). The Present study showed significant association of psychiatric morbidities in these two dermatological diseases (psoriasis and vitiligo) with the variables of the study population. Conclusion: It has been found in Bangladesh that the psychiatric morbidity is higher among the patients with psoriasis than vitiligo. Key words: Psoriasis; Vitiligo; Psychiatric morbidity DOI: http://dx.doi.org/10.3329/bsmmuj.v4i2.8636 BSMMU J 2011; 4(2):88-93